Decoding Financial Performance: The Role of Leverage and Market Risk in Indonesia's LQ45 - Budiman Budiman; Farah Margaretha (Jurnal Akuntansi dan Keuangan, 2024)
This study examines the determinants of financial performance in LQ45 Index companies from 2018–2022. It focuses on factors such as equity multiplier, interest coverage, financial leverage, fixed charge coverage, debt to EBITDA, capitalization ratio, and market risk. Control variables include company age, sales growth, and firm size. Using multiple regression analysis on data from 48 companies, the study finds that interest coverage, fixed charge coverage, market risk, company age, and sales growth positively impact financial performance, while financial leverage, debt to EBITDA, capitalization ratio, and firm size have a negative effect. The equity multiplier shows no significant influence. The findings suggest maintaining high interest and fixed charge coverage ratios and effective risk management to enhance financial performance. Careful management of high debt to EBITDA levels is necessary to prevent negative impacts. Investors should consider these factors when assessing a company's financial health.